Efficacy Analysis of Current Therapeutic Modalities for SARS-CoV-2 Infection - Bhadauriya, Anshika (Journal of Social Science and Humanities, 2025)
SARS-CoV-2 (COVID) has been at the forefront of medical discussion and research after the onset of the global pandemic. With many individuals not vaccinated for COVID, it became important to determine what treatment options are available for the treatment of COVID, what the efficacy of these treatment options is, and to determine which of these options does not hold any benefit in administration for patients hospitalized with COVID. Efficacious treatment options were determined by decreased hospital stay of the patient, decreased overall mortality of patient when receiving the treatment compared to a placebo, decreased oxygen use, or had a shorter hospital course leading to discharge earlier. An analysis of the literature revealed that treatment options that were found to have an efficacious effect on treating COVID were antibody therapy, cell therapy, Paxlovid, Remdesivir, Hydroxychloroquine used with Azithromycin, Favipravir, Sofosbuvir and Daclastasivir, Tocilizumab, drinking tea, edaravone, IL1, IL6 inhibitors, teicoplanin, low and high dose dexamethasone, methylprednisolone, as well as ivermectin. There was most support for the use of remdesivir, followed by hydroxychloroquine, and then low dose dexamethasone. The literature strongly suggested against the use of Lopinavir-Ritonavir. Further research is recommended for the use of Hydroxychloroquine with Azithromycin, though thus far the research has been generally supporting its use in the treatment of COVID. Further research is also suggested in the treatment of Ribavirin.